Sir Gadabout does his best - Beardsley, Martyn; Ross, Tony (London : Orion Children's Books, 2006)
Sir Gadabout, the worst knight in the kingdom, sets off on a chaotic adventure with a three-legged goat, a hungry dragon, and a knight named Sir Mistabit.
4.7
3-6
Keywords: Adventure and adventurers -- Fiction; Humorous stories; Knights and knighthood -- Fiction; Adventure fiction; Humorous fiction; Knights and knighthood -- Fiction